2020
DOI: 10.21577/0103-5053.20190256
|View full text |Cite
|
Sign up to set email alerts
|

Methodology Development and Validation of Amphotericin B Stability by HPLC‑DAD

Abstract: The high worldwide consumption of antibiotics and their complex impurity profiles has drawn the attention of the scientific community to the development and validation of stability methods for these drugs. Amphotericin B is an antibiotic that is a natural fermentation product of bacterium Streptomyces nodosus, used as a broad-spectrum antifungal agent, and is highly unstable. For this reason, the objective of this work is the development and validation of an indicative method of stability by high performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results that were obtained were coherent with those published initially by Chang et al in terms of retention times and relative retention times, and breakdown studies allowed the detection of multiple compounds, all correctly separated from the main amphotericin B peak. They are also in accordance with the results of a very recent study by Montenegro et al who also developed a stability indicating liquid chromatography–diode array detector method for amphotericin B quantification [ 37 ]. They confirmed that amphotericin B degrades rapidly under acidic, alkaline, oxidative and radiation exposure conditions, detecting 16 breakdown products, and made an interesting tentative shot at identifying some of the compounds using direct injection electrospray ionization mass spectrometry and electrospray ionization tandem mass spectrometry.…”
Section: Discussionsupporting
confidence: 90%
“…The results that were obtained were coherent with those published initially by Chang et al in terms of retention times and relative retention times, and breakdown studies allowed the detection of multiple compounds, all correctly separated from the main amphotericin B peak. They are also in accordance with the results of a very recent study by Montenegro et al who also developed a stability indicating liquid chromatography–diode array detector method for amphotericin B quantification [ 37 ]. They confirmed that amphotericin B degrades rapidly under acidic, alkaline, oxidative and radiation exposure conditions, detecting 16 breakdown products, and made an interesting tentative shot at identifying some of the compounds using direct injection electrospray ionization mass spectrometry and electrospray ionization tandem mass spectrometry.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that AmB suffers from degradation when exposed to light, heat, radical initiators, and extreme pH conditions. The by-products have not been isolated yet, but the most probable reactions involve the highly conjugated polyene backbone, similar to a lipid oxidation [ 27 ]. Moreover, previous studies suggested that the degradation products may increase drug toxicity, such as acute hemolysis [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chromatographic conditions used in this study were based on those reported by Espada et al, with some changes [ 29 ]. The detection wavelength for AmB and its related impurities, eventually present during in-use conditions storage, was set at 406 nm, as already proposed for the detection of some degradation products [ 27 ]. Linearity was maintained with stock solutions in methanol ranging from 38 to 360 µg/mL AmB.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed insignificant degradation of AMB in the presence of water [230]; this fact could be related to AMB's low solubility in aqueous and neutral pH vehicles. Exposure of AMB to ± 70°C for up to 7 days did not provoke thermal degradation.…”
Section: Stabilitymentioning
confidence: 99%